Influence of source of nutrition on potato (Solanum tuberosum) tuber quality in elevated temperature storage - BANDANA, BANDANA; KUMAR, DINESH; KUMAR, PARVEEN; RAWAL, SANJAY; SAINI, NEERAJ; SHARMA, VINEET (The Indian Journal of Agricultural Sciences, 2018)
Field experiment was conducted for two years at Central Potato Research Institute Campus, Modipuram to study the effect of organic+homeopathic and inorganic treatments on potato. Potato (Solanum tuberosum L.) harvested after curing were stored at elevated temperature (12Â±0.5oC) with CIPC, (Isopropyl-N-(3-chlorophenyl carbamate) as per modern technology adopted by farmers. The experiment was laid out in sub-plots with three sources of nutrition (organic+homeopathic nutrition) and inorganic treatments and three cultivars Kufri Bahar, Kufri Sindhuri and Kufri Chipsona-3 in main plots. Results showed that dry matter responded positively to inorganic treatment over organic. Variety Kufri Chipsona 3 recorded maximum dry matter followed by Kufri Sindhuri, while lowest dry matter was reported in Kufri Bahar. Organic and homeopathic nutrition resulted in significantly superior chip colour as compared to inorganic treatment. During both the years, potato chips prepared from cv. Kufri Chipsona 3 tubers with organically treated one had better chip colour. Organic and homeopathic nutrition significantly reduced mean reducing sugars in stored potatoes as compared to inorganic treatment. During both the years of experiment, reducing sugars were low in organically fertilized potatoes in comparison to inorganically fertilized crop. Mean sucrose content in potatoes stored at this temperature was at par in first year, while significantly lower values were observed in second year of experiment in organic+homeopathic treatment. Phenols content were significantly lower in organic and homeopathic treatment over inorganic nutrition across the genotypes in both the years during storage.